2022
DOI: 10.2991/absr.k.220102.023
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Cassava Var. Gajah (Manihot esculenta C) Derivative Products as a Thickening Agent in the Manufacturing of Tamarind (Tamrindicus indica) Paste

Abstract: Cassava var. Gajah (Manihot esculenta C) is a typical crop of East Kalimantan which has potential to be developed into a carbohydrate-based agricultural industry commodity. However, the cassava var. Gajah has not been used optimally, and limited research has been done. We conducted this research to utilize cassava derivatives products namely cassava starch and cassava flour as a natural thickening agent (NTA) in tamarind pasta making. The characteristics of paste obtained were identified: its viscosity, water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The highest viscosity is in the addition of modified starch with a value of 5624 mPa's at a concentration of 10% while the viscosity of the addition of mocaf is lower with a value of mPa's at a concentration of 10%. In previous research (Prabowo et al, 2022) the lowest viscosity value was found in the control sample 2.45 Pa.s and the highest viscosity was found in tamarind paste with the addition of cassava starch thickener with a concentration of 5% 8.58 Pa.s. This is because natural flour has an ammonium content.…”
Section: Results and Discussion 1 Physical Characteristicsmentioning
confidence: 78%
See 4 more Smart Citations
“…The highest viscosity is in the addition of modified starch with a value of 5624 mPa's at a concentration of 10% while the viscosity of the addition of mocaf is lower with a value of mPa's at a concentration of 10%. In previous research (Prabowo et al, 2022) the lowest viscosity value was found in the control sample 2.45 Pa.s and the highest viscosity was found in tamarind paste with the addition of cassava starch thickener with a concentration of 5% 8.58 Pa.s. This is because natural flour has an ammonium content.…”
Section: Results and Discussion 1 Physical Characteristicsmentioning
confidence: 78%
“…This is due to the use of the same amount of tamarind raw material in the form of puree in each treatment and the temperature used during gelatinization tends to be the same. In previous research (Prabowo et al, 2022) at concentrations of 3% and 5% addition of thickening agents, the solubility of tamarind paste did not experience a significant difference compared to the addition of 1% thickening agents for both cassava flour and cassava flour. Changes in solubility occur due to the amylose and amylopectic content of the thickener and the gelatinization temperature used in the processing process.…”
Section: Results and Discussion 1 Physical Characteristicsmentioning
confidence: 80%
See 3 more Smart Citations